Close to me: the effect of asymmetrical environments on spatial attention. - Nicholls, M; Roden, S; Thomas, N; Loetscher, T; Spence, C; Forte, J (2014)
UNLABELLED: Attention can be captured by distractors and can affect performance. To examine whether asymmetrical distractors, such as a wall, affect spatial attention, Experiment 1 required participants (n = 20) to determine the relative length of pre-bisected lines when a temporary barrier was placed close to the left or right sides of the display. Post-hoc tests showed that attention was drawn towards left, but not right, walls. Experiment 2 (n = 18) sought to increase this effect using a solid brick wall rather than a temporary barrier. Instead of strengthening the result, no effect of barrier was observed. A non-effect was also observed in Experiment 3 (n = 18) when participants moved a cursor to the line's middle. Finally, Experiment 4 (n = 26) showed that asymmetrical barriers had no effect on visual search. While the data showed some evidence that attention is distracted by walls placed to the left, this effect is weak and task-specific. PRACTITIONER SUMMARY: The ability to monitor critical information on displays can be affected by asymmetrical distractors. In many workplaces, a display may be placed alongside a wall. This study explored whether a wall placed to the left/right affects spatial attention. A weak, task-specific, attraction effect was observed for walls on the left.